AAAprawda. Telemetria prawdy - Michaluk, Tomasz (Humaniora. Czasopismo Internetowe, 2019)
Developed societies are not interested in the truth. The demand for truth has disappeared while its causal role has been marginalized and limited to the authentication of identity in banking systems and social media. Exactly a century earlier, due to due to fallibilism or falsificationism, science rejected the Cartesian conception of Absolute truth, while retaining its objectivity although not the stability of its findings. Today, we intersecting worlds, but not identical in values. The reason for this is not the inability to work out a common research method but an axiological redefinition, which often comes down to the question: truth and so what?